Investigation of the Filamin A–Dependent Mechanisms of Tissue Factor Incorporation into Microvesicles - Collier, Mary E. W.; Ettelaie, Camille; Goult, Benjamin T.; Maraveyas, Anthony; Goodall, Alison H. (Thrombosis and Haemostasis, 2017)
We have previously shown that phosphorylation of tissue factor (TF) at Ser253 increases the incorporation of TF into microvesicles (MVs) following protease-activated receptor 2 (PAR2) activation through a process involving filamin A, whereas phosphorylation of TF at Ser258 suppresses this process. Here, we examined the contribution of the individual phosphorylation of these serine residues to the interaction between filamin A and TF, and further examined how filamin A regulates the incorporation of TF into MVs. In vitro binding assays using recombinant filamin A C-terminal repeats 22–24 with biotinylated phospho-TF cytoplasmic domain peptides as bait showed that filamin A had the highest binding affinities for phospho-Ser253 and double-phosphorylated TF peptides, while the phospho-Ser258 TF peptide had the lowest affinity. Analysis of MDA-MB-231 cells using an in situ proximity ligation assay revealed increased proximity between the C-terminus of filamin A and TF following PAR2 activation, which was concurrent with Ser253 phosphorylation and TF-positive MV release from these cells. Knock-down of filamin A expression suppressed PAR2-mediated increases in cell surface TF procoagulant activity without reducing cell surface TF antigen expression. Disrupting lipid rafts by pre-incubation with methyl-β-cyclodextrin prior to PAR2 activation reduced TF-positive MV release and cell surface TF procoagulant activity to the same extent as filamin A knock-down. In conclusion, this study shows that the interaction between TF and filamin A is dependent on the differential phosphorylation of Ser253 and Ser258. Furthermore, the interaction of TF with filamin A may translocate cell surface TF to cholesterol-rich lipid rafts, increasing cell surface TF activity as well as TF incorporation and release into MVs.
Keywords: tissue factor; filamin A; microvesicles; protease-activated receptor 2; lipid rafts